Navigating the Digital Marketplace: A Comprehensive Review of E-Commerce Trends, Challenges, and Innovations - Zangana, Hewa Majeed; Natheer Yaseen Ali; Ayaz khalid Mohammed (Universitas Airlangga, 2024)
Background: Comprehensive exploration of e-commerce landscape; Insights drawn from diverse scholarly sources across disciplines. Objective: Examine key themes, including COVID-19 impact, consumer behavior, business models, regulatory challenges, security, privacy, opportunities, and future trends in digital commerce. Method: The methodology involved a comprehensive literature review spanning various disciplines to explore e-commerce. Scholarly sources were gathered from academic databases and journals, focusing on key themes like the COVID-19 impact, consumer behavior, business models, regulatory challenges, security, privacy, opportunities, and future trends. Data analysis identified patterns and trends, with findings organized into distinct sections. Synthesizing and interpreting the results within the e-commerce context, along with peer feedback, ensured the study's rigor and credibility. Results: Uncover sustained shift in consumer preferences influenced by the pandemic; Provide insights into strategic approaches adopted by businesses in the digital marketplace. Conclusion: Anticipate future e-commerce trajectory, discussing emerging trends like metaverse integration, AI, augmented reality shopping, voice commerce, and online-offline convergence; Serve as a guide for businesses navigating challenges, seizing opportunities, and aligning with emerging trends; Offer a comprehensive understanding of the dynamic nature of e-commerce in the digital age. Keywords: Artificial Intelligence; Business; E-Commerce; Marketing.